Kajian Perspektif Islam Dalam Tradisi Lomban di Desa Ujungbatu, Kabupaten Jepara - Muhammad Fathul Mujib; Muhammad Vicky Yakhya; Yusuf Falaq (Publikasi Inspirasi Indonesia, 2023)
One of the many activities during the Lomban Festival, which takes place every year on the 8th of Shawwal, is larung sesaji in Jepara city. The purpose of this research is to find out more about the implementation of the Lomban Festival, its purpose, and the history of larung sesaji. This research is a literature research using a literature review approach. In the city of Jepara, where most of the population are fishermen, many ancient cultural customs are still practiced today. Larung sesaji during the Lomban Festival is one of these customs. This tradition is said to have started when officials from Jepara were caught in a storm while trying to cross to Karimunjawa.